Diaspora to Transnational Networks: the Case of Chinese Diaspora in the Mainland China - Mathew, P A (Ushus Journal of Business Management, 2005)
Out of the many views on globalization, the one that focuses on the network approach is different in scope. This approach focuses on the social embeddedness of the profit oriented business world rather than giving Multinational Corporations the central role in the globalization process. Changes in the world economy have brought in new players in the competitive market place and one of the players is the Diaspora investors. The Diaspora investors unliie the traditional business players use network relations to survive and succeed in the dynamic global economy. An excellent example for this is the case of Chinese Diaspora. They were able to carve a niche for themselves in the mainland China when the economy opened up. By using network relations and making connections horizontally across the vertical walls of a segmented society they were able to promote transnational linkages. This article focuses on the utilization Guanxi as a cultural strategy for securing social resources towards goal attainment.